2019
DOI: 10.3390/nano9121784
|View full text |Cite
|
Sign up to set email alerts
|

The Flexible Lubrication Performance of Graphene Used in Diamond Interface as a Solid Lubricant: First-Principles Calculations

Abstract: The interfacial friction performances of graphene covered and hydrogen-terminated diamond surfaces were investigated comparatively by first-principles calculations within density functional theory (DFT). Both systems exhibit similar excellent lubricating effects under small load, but the graphene covered interface presents small friction than that of hydrogenated system for the larger load. The calculated interfacial friction between two sheets of graphene covered diamond surface increases slowly than that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The same collective also elucidated the atomistic mechanism behind the experimentally observed low friction of these all-carbon lubricants [110]. The low friction at the GN-diamond interface was also proposed by DFT calculations [99] and by molecular dynamics simulations [111]. The theoretical studies suggested that the best lubricity is attained when the GN slides along its armchair direction.…”
Section: Friction Tribology and Mechanical Propertiesmentioning
confidence: 64%
See 1 more Smart Citation
“…The same collective also elucidated the atomistic mechanism behind the experimentally observed low friction of these all-carbon lubricants [110]. The low friction at the GN-diamond interface was also proposed by DFT calculations [99] and by molecular dynamics simulations [111]. The theoretical studies suggested that the best lubricity is attained when the GN slides along its armchair direction.…”
Section: Friction Tribology and Mechanical Propertiesmentioning
confidence: 64%
“…The rather weak interaction between the two nanocarbon allotropes determines the unique mechanical performance of these hybrid materials thanks to sliding-induced graphitization and passivation of dangling bonds [99]. Thus, the interface is responsible for the GN-diamond heterostructures' outstanding lubrication and mechanical properties; this topic will be discussed in the first part of this section.…”
Section: Graphene-diamond Interfaces and Heterojunctionsmentioning
confidence: 98%
“…An alternative for friction reduction at the interface of sp 3 -bonded carbon was suggested by the DFT study conducted by Wang et al [96]. A graphene layer inserted between two carbon surfaces was compared to the same surface but with hydrogen passivation instead.…”
Section: Lubricantsmentioning
confidence: 99%
“…Therefore, it is necessary to understand the friction properties of diamane for its application in MEMS/NEMS. After inheriting excellent lubricant properties of its bulk graphite, graphene has been considered as one of the most promising nanoscale lubricating materials [ 2 , 22 ], which can be used as an excellent coating lubricant to reduce interface friction and wear [ 23 , 24 ]. Diamond single crystal (DSC) film also has low friction and high wear resistance properties [ 25 ], which can be understand by the mechanisms of the sliding-induced graphitization [ 26 , 27 ] and passivation of dangling bonds [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%